R.E. Bloomfield diaries - Bloomfield, R. E. (Robert E.)
Diaries kept by Bloomfield while serving as an electrician aboard the battleship Vermont. One diary (1907-1908) kept during a tour of the Great White Fleet and a second diary (1908-1911) during a voyage to Cuba, England, and France. Diaries include photographs, newspaper clippings, maps, and foreign postage stamps.
Electrician, U.S. Navy.
Collection material in English.
Forms part of: Naval Historical Foundation collection.
Keywords: United States. -- Navy -- History; Vermont (Battleship); Voyages around the world; Cuba -- Description and travel; England -- Description and travel; France -- Description and travel; United States -- History, Naval; Electricians